Korelasi antara Efikasi Diri dengan Kemampuan Berpikir Kreatif Matematis Siswa pada Materi Statistika - Vauriska, Fiona Rizki; Meilasari, Venty (Universitas Muhammadiyah Kotabumi, 2025)
This study aims to determine the correlation between self-efficacy and students mathematical creative thinking abilities in statistics material for class Vlll MTsN 3 North Lampung in the 2024/2025 academic year. The research method used is a quantitative method with a correlational design. The study population included all class Vlll MTsN 3 North Lampung students in the 2024/2025 academic year with a total of 223 students. The sample selected from the entire population of MTsN 3 North Lampung amounted to 70 students obtained from the quota sample technique. The data collection technique in this study used a questionnaire instrument with a likert scale model for self-efficacy and a descriptive test instrument for creative thinking abilities. Before testing the hypothesis, a normality test was first carried out using the liliefors test and a linearity tests. The results of this study indicate that there is a correlation between self-efficacy and mathematical creative thinking abilities with a correlation coefficient . This indicates a relationship between self-efficacy and students mathematical creative thinking skills in statistics for grade Vlll students at MTsN 3 North Lampung in the 2024/2025 academic year.